Emodin Rescues Intrahepatic Cholestasis via Stimulating FXR/BSEP Pathway in Promoting the Canalicular Export of Accumulated Bile - Xiong, Xiao-Li; Ding, Yan; Chen, Zhi-Lin; Wang, Yao; Liu, Pan; Qin, Huan; Zhou, Li-Shan; Zhang, Ling-Ling; Huang, Juan; Zhao, Lei (Frontiers in Pharmacology, 2019)
Aims: Bile salt export pump (BSEP) have been confirmed to play an important role for bile acid canalicular export in the treatment of cholestasis. In this study, we investigated the stimulatory effect of Emodin on BSEP signalling pathway in cholestasis. Methods: Cell and animal experiments were given different concentrations of Emodin. The BSEP upstream molecule farnesoid X receptor was down-regulated by small interfering RNA (siRNA) technology or guggulsterones and up-regulated by lentivirus or GW4064. Real-time PCR and Western blotting was employed to detect the mRNA and protein levels of BSEP in LO2 cell, rat primary hepatocytes and liver tissue. Immunohistochemistry (IHC) was used to examine the expression of BSEP in liver tissues. Rat liver function and pathological changes of liver tissue were performed by biochemical test and haematoxylin and eosin (HE) staining. Results: Eomdin could increase the mRNA and protein expression of BSEP and FXR. When down-regulating farnesoid X receptor expression with the siRNA or inhibitor guggulsterones, and up-regulating farnesoid X receptor expression with the lentivirus or agonist GW4064, Emodin could increase the mRNA level of BSEP and FXR and the protein level of BSEP, FXR1 and FXR2. Emodin also had a notable effect on rat primary hepatocytes experiment, rat pathological manifestation, BSEP, FXR1 and FXR2 positive staining in liver tissues and the test of liver function. Conclusions: Emodin has a protective effect and a rescue activity on cholestasis via stimulating FXR/BSEP pathways in promoting the canalicular export of accumulated bile.